"THE EXPRESSION OF COLORS IN THE MURALS OF VARANASI": ‘‘रंगों की अभिव्यक्ति वाराणसी के भित्ति चित्रों में’’ - Gupta, Ishwar Chand (International Journal of Research -GRANTHAALAYAH, 2014)
Color is the soul of the picture, human attachment to colors has been there since time immemorial. The prevalence of colors is very old in Indian civilization and culture. Colors indicate our happiness in life, our companions. Their sixth is scattered around on social festivals. Rangoli is made at the entrance on the occasion of auspicious work or guest arrival. Colors fill our life with happiness and energy. Indian spirituality is also drenched with different colors. Many colors are present in the universe. The basis of Indian color psychology is nature. In nature, we see many colors in the sky, some of which appear to be anti-nature. Human attraction to colors has never diminished, from primitive cavities to modern humans took the support of colors (varnas) in the development of beauty. The human mind has always been eager to know the secret of colors. In 1670, a scientist named 'Sir Isaac Newton' first removed the mystery of the origin of colors. He believes that the color (color) originates from light. 1 All the colors that appear in nature are different parts of light. Realization comes from sunlight, that is, sunlight is considered to be the origin of colors. It is well known that there are seven colors in sunlight, but these seven colors are not visible to us because the earth revolves around the sun. And because of this rotation, these seven colors are not visible, all these colors are grouped in seven colors, which are not visible, but appear in the form of light (sunshine), seven colors of the rainbow in the sky in the rainy days. can be seen. The color scheme continues to develop along with the development of culture. Man seems to be absorbed in the color scheme from time immemorial. He enjoys developing his colors with culture, civilization. From the early twentieth century, artists began to use colors in a more developed form. रंग चित्र की आत्मा है, रंगों के प्रति मनुष्य आसक्ति आदिम समय से ही रहा है। भारतीय सभ्यता एवं संस्कृति में रंगों का प्रचलन बहुत पुराना है रंग हमारे जीवन के साथी, ये हमारे सुखों को इंगित करते हैं। सामाजिक उत्सवांे-पर्वों पर इनकी छठा चारों ओर बिखरी होती है। शुभ कार्य हो या अतिथि आगमन पर प्रवेश द्वार पर रंगोली बनाई जाती है रंग हमारे जीवन में खुशी एवं ऊर्जा भर देते हैं भारतीय आध्यात्म भी विभिन्न रंगों से सराबोर है। सृष्टि में अनेक रंग मौजूद हैं भारतीय रंग मनोविज्ञान का आधार प्रकृति है प्रकृति में अनेक रंगों को आकाश में देखते हैं जिनमें से कुछ विरोधी प्रकृति के दिखते हैं। रंगों के प्रति मानव का आकर्षण कभी कम नहीं हुआ, आदिम गुहावासियों से लेकर आधुनिक मानव ने सौन्दर्य के विकास में रंगों (वर्णों) का सहारा लिया। रंगों के प्रति रहस्य जानने के लिए मनुष्य का मन सदैव उत्सुक रहा है। सन् 1670 में ‘सर आइजक न्यूटन’ नामक वैज्ञानिक ने सर्वप्रथम रंगों के उत्पत्ति का रहस्य हटाया उनका मानना है कि वर्ण (कलर) की उत्पत्ति प्रकाश से होती है।1 प्रकृति में जितने भी रंग दिखाई देते हैं वे प्रकाश के विभिन्न अंग हैं प्रकाश की प्राप्ति सूर्य की रोशनी से होती है अर्थात् सूर्य की रोशनी ही रंगों का उद्गम माना गया है यह सर्वविदित है कि सूर्य की रोशनी में सात रंग होते हैं, किन्तु यह सात रंग इसलिए हमें नहीं दिखाई देते हैं कि पृथ्वी सूर्य के चारों ओर चक्कर लगाती है और इसी घूमने के कारण यह सातों रंग दिखाई नहीं पड़ते हैं इन सब रंगों का समूह सात रंग की पट्टीयाॅ होती हैं जो दिखाई नहीं पड़ते हैं, बल्कि प्रकाश (धूप) के रूप में दिखाई देते हैं इन्द्रधनुष के सात रंग वर्षा के दिनों में आकाश में दिखाई देते हैं। संस्कृति के विकास के साथ-साथ रंग योजना भी विकसित होती रहती है। मनुष्य अनादि काल से रंग योजना में लीन दिखाई देता है। उसे अपने रंगों को संस्कृति, सभ्यता के साथ विकास देने में आनन्द आता है। बीसवीं शताब्दी के आरंभ से ही कलाकारों ने रंगों का उपयोग अधिक विकसित रूप में करना शुरू किया।